Paleografia e evolução da paisagem do nordeste do estado do Pará e noroeste do Maranhão: cretáceo ao holoceno - SOARES JUNIOR, Adilson Viana (2002)
This research presents some aspects of the tectonics and paeleogeographic evolution of northeastem region of Pará State and northwestem region of Maranhão State in the northem Brazil, based on the integration of structural, tectonic, stratigraphic, sedimentological and paeleontological data. The Marajó basin is elongated in a NW-SE direction and includes a sedimentary sequence deposited ffom Upper Cretaceous to Upper Tertiary. The geometry of the Marajó Basin is characterised by NW-SE normal faults in the northwest-southeast direction and NE-SW and ENE-WSW strike-slip faults, which define the boundaries ofthe Mexiana, Limoeiro, Cametá and Mocajuba sub-basins. The Gurupi Graben System encompasses the Bragança-Viseu, São Luís and Ilha Nova basins, with Cretaceous and Tertiary sedimentary filling. The Bragança-Viseu Basin is formed by two assymmetric grabens - the Caeté depocenter (close to the northem border) and the Piriá depocenter, close to the southem limit - in a NW-SE direction, separated by a transcurrent fault. The São Luís Basin comprises three sub-basins: Maracaçumé, in the northwest, Bacuri, in the northeast, and Bequimão, toward the southeast. The Ilha Nova basin is divided into two halfgrabens separated by a transcurrent fault. The westem half-graben presents antithetic faults in the southem and northem borders, while these faults ocurr only in its northem extreme ofthe eastem halfgraben. The Grajaú Basin is an extensional feature of the Cretaceous, generated by normal fault propagation towards the continent interior, during the opening ofthe Equatorial Atlantic, and by partial reactivation of the Paleozoic structures of the Pamaíba basin. The stratigraphy is composed ofthe Grajaú, Codó and Itapecurú formations, controled by N-S planar normal faults, diping to the west, and linked through NE-SW transcurrent faults. The Gurupá Are strikes NW-SE, correspond to the boundary ofthe Amazon Basin, and defines the shoulder ofthe Marajó basin, closely associated with listric faults. Northem Marajó encompasses the region between the northeastem shoulder of the Marajó Basin and the Pará/Ilha de Santana Platform, and is characterised by neotectonic structures represented by NE-SW transcurrent faults, as those that control the mouth of the Tocantins river towards the northeast. 4 The Tocantins Are is a positive feature that bounds the Marajó and Grajaú basins, and corresponds to a transpressive region. The Gurupi Are is a positive feature that limits the Bragança-Viseu and São Luís basins, running in a NNE-SSW direction, and worked as an area wich accomodated high strain during the Cretaceous. The Ferrer-Urbano Santos Are is an E-W positive feature that limits the São Luís and Grajaú basins formed during the Cretaceous, with an axis of uplifting that migrated southwards through the time. The partial collapse ofthis are evolved to the São Luís Basin. The Tiracambú Hills derived from Grajaú Basin inversion, since the Paleocene, wich resulted in the propagation ofE-W transcurrent dextral systems and was followed by the tectonic calm that originated the mature lateritic profile. The Estrondo Hills is related to N-W normal faults, and is interpreted as derived by reactivation of older struetures during the Cretaceous-Upper Tertiary extensional event, controlling the courses ofthe Araguaia and Tocantins rivers